Effects of Facial Expression and Language on Trustworthiness and Brain Activities. (7th June 2015) - Morioka, Shu; Osumi, Michihiro; Okamoto, Mari; Matsuo, Atsushi
Abstract : Social communication uses verbal and nonverbal language. We examined the degree of trust and brain activity when verbal and facial expressions are incongruent. Fourteen healthy volunteers viewed photographs of 8 people with pleasant (smile) or unpleasant expressions (disgust) alone or combined with a verbal [positive/negative] expression. As an index for degree of trust, subjects were asked to offer a donation when told that the person in the photograph was troubled financially. Positive emotions and degree of trust were evaluated using the Visual Analogue Scale (VAS). Event-related potentials (ERPs) were obtained at 170–240 ms after viewing the photographs. Brain activity during incongruent conditions was localized using standardized Low Resolution Brain Electromagnetic Tomography (sLORETA). VAS scores for positive× smile condition were significantly higher than those for the other conditions (p < 0.05 ). The donation offered was significantly lower for incongruence between verbal and facial expressions, particularly for negative× smile condition. EEG showed more activity in the parietal lobe with incongruent than with congruent conditions. Incongruence [negative× smile] elicited the least positive emotion, degree of trust, and amount of offer. Our results indicate that incongruent sensory information increased activity in the parietal lobe, which may be a basis of mentalizing.